Altered metabolic profiles of dermatomyositis with different myositis-specific autoantibodies associated with clinical phenotype - Wang, Nan; Shang, Lili; Liang, Zhaojun; Feng, Min; Wang, Yanlin; Gao, Chong; Luo, Jing (Frontiers in Immunology, 2024)
IntroductionDermatomyositis (DM) is an idiopathic inflammatory myopathy. Because of clinical heterogeneity, the metabolite profile of DM patients with different myositis-specific autoantibodies (MSAs) remains elusive. This study aimed to explore the metabolomics characteristics of the serum in DM with different MSAs, low or high disease activity, and interstitial lung disease.MethodsUntargeted metabolomics profiling was performed in the serum of a discovery cohort (n=96) and a validation cohort (n=40), consisting of DM patients with MSAs, low or high disease activity, and/or interstitial lung disease (DM-ILD) compared to age- and gender-matched healthy controls (HCs).ResultsThe lipid profile in DM was found to be abnormal, especially dysregulated glycerophospholipid metabolism and fatty acid oxidation, which might affect the pathogenesis of DM by disrupting the balance of Th17 and Treg. We identified potential biomarkers of DM that can distinguish between low or high disease activity and reflect lung involvement. Two metabolite combinations including pro-leu, FA 14:0;O can distinguish high disease activity DM from low disease activity DM and HCs, and five including indole-3-lactic acid, dihydrosphingosine, SM 32:1;O2, NAE 17:1, and cholic acid can distinguish DM-ILD from DM without ILD (DM-nonILD). DM with different MSAs had unique metabolic characteristics, which can distinguish between MDA5+DM, Jo-1+DM, and TIF1-γ+DM, and from the antibody-negative groups. The sphingosine metabolism has been found to play an important role in MDA5+DM, which was associated with the occurrence of ILD.DiscussionAltered metabolic profiles of dermatomyositis were associated with different myositisspecific autoantibodies, disease activity, and interstitial lung disease, which can help in the early diagnosis, prognosis, or selection of new therapeutic targets for DM.